Registration of Strigaresistant and Droughttolerant tropical early maize populations TZEW Pop DT STR C4 and TZEY Pop DT STR C4 - Badu-Apraku, Baffour; Yallou, C.G. (Wiley, 2009)
Two maize (Zea mays L.) populations, TZE-W Pop DT STR C4 (Reg. No. GP-574, PI 654407), white- grained, fl int/dent, and TZE-Y Pop DT STR C4 (Reg. No. GP-575, PI 654408), yellow-grained, fl int/dent with drought tolerance and moderate levels of resistance to the fl owering parasitic witchweed, Striga hermonthica (Del.) Benth, were developed at the International Institute of Tropical Agriculture (IITA). The two breeding populations were released to national maize programs in west and central Africa as source germplasm in 2004 for the development of Striga-resistant synthetic varieties, parental inbred lines, and hybrids. The populations were released for their superior grain yield under Striga-infested and noninfested conditions. They also have good levels of resistance to maize streak virus, tropical lowland rust (incited by Puccinia polysora Underw.), and blight [caused by Bipolaris maydis (Nisikado & Miyake) Shoemaker]. In multilocation trials in Benin Republic and Nigeria, 2006 and 2007, TZE-W Pop STR C4 outyielded the Striga-susceptible check TZE Comp. 4 by 44% under Striga infestation and 12% when noninfested. Under the same conditions, the increased yield for TZE-Y Pop DT STR C4 was 42% (Striga infested) and 16% (noninfested). The check variety TZE Comp. 4 suffered the highest Strigadamage and supported the highest number of emerged Striga plants when Striga infested.